REVIVAL OF UZBEK FOLK GAMES IN THE PRESENT PERIOD (GAMES TRANSMIT VALUES AND CULTURE TO THE YOUNG) - Mehri Kurbanova Ph D (Scholar Express Journal, 2022)
Uzbek folk games have been played on various holidays for thousands of years. Currently, a lot of work is being done to develop these games and distribute them throughout Central Asia and the rest of the world. The purpose of these folk games is to bring people together, improve their health and help preserve the cultural heritage of the people.
Keywords: Folk games; physical culture and sport; national value